Genetic differences in lung adenocarcinoma cells from patients of African and European ancestry - Diseko, Karabo (Department of Integrative Biomedical Sciences (IBMS), 2025)
In the past two decades, advancements in cancer genetics research have significantly enhanced our molecular comprehension of human cancers. This progress has led to the development of improved clinical tools for the precise diagnosis, prognosis prediction, and tailored treatment of cancers. However, the predominant focus of this research has been on individuals of European ancestry, inadvertently marginalizing the diverse genetic landscapes represented by other ethnic populations. Given minor differences in the genetic makeup across diverse ethnicities, specific cancer genetic variants prevalent in certain ethnic groups may remain overlooked within the current research. Some studies have indeed illuminated nuanced distinctions in the genetic architecture of cancers among patients of varying ethnic backgrounds. Disparities in cancer incidence and outcome between patients of different ethnicities have also been identified. These distinctions stem from a combination of environmental and biological factors, collectively shaping the intricate interplay of cancer genetics and its clinical manifestations. This study endeavours to elucidate clinically significant disparities in lung adenocarcinoma (LUAD) genetics across distinct ethnicities, particularly focusing on African ancestry (AA) and European ancestry (EA) populations. A meticulous comparison of genetic traits within LUAD cells derived from these ethnic groups is conducted to pinpoint genetic variances that hold potential biological relevance. Leveraging data from The Cancer Genome Atlas' lung adenocarcinoma (TCGA-LUAD) study, samples were stratified based on self-reported racial classifications into African ancestry (AA) and European ancestry (EA) groups. Propensity score matching (PSM) was meticulously employed to mitigate disparities in crucial clinical attributes, ensuring a balanced basis for subsequent genetic comparisons. A total of 147 EA and 49 AA samples were extracted following PSM, forming the basis for comprehensive comparisons of gene expression, copy number alterations, and mutation frequencies between the two ethnic cohorts. Key genetic disparities between the two groups were discerned, including 371 significantly differentially expressed (SDE) genes, a higher incidence of copy number alterations in the AA group compared to the EA group, and 101 genes exhibiting varying mutation frequencies between the two groups. An analysis of the biological functions impacted by these genetic variances revealed involvement in critical processes such as cellular response to xenobiotics, hormone metabolism and regulation, mitochondrial energy production, and epithelial-mesenchymal transition. We posit that clinically relevant biological distinctions in LUAD tumours between AA and EA patients stem from differential expression and mutations in genes encoding pivotal proteins such as UDP glucuronosyltransferases and cytochrome P450s, among others. Variations in the sequence and expression of these genes can significantly influence drug response and hallmark cancer cell characteristics, including energy production and epithelial-mesenchymal transition. Despite the limitation of a relatively small sample size, this study illuminates genetic disparities that underpin clinically significant differences in tumour biology between LUAD patients of African and European ancestry.